Mindfulness-Based Cognitive Therapy for Depression Symptoms in Patients with Persistent Depression Disorder - Nastaran Kharaman; Davood Taghvaei; Mehdi Jahangiri (Iranian Evolutionary Educational Psychology Journal, 2022)
Preceding studies have indicated that cognitive therapy can be as effective as medications for depression. The combination of cognitive therapy and mindfulness practices has been shown to effectively manage persistent depression. This study aimed to examine effectiveness of mindfulness-based cognitive therapy on the depressive symptoms in patients with persistent depressive disorder. The research method was a semi-experimental pre-test-post-test with a control group design. The statistical population of the study included all patients with persistent depressive disorder that referred to psychology and psychiatry clinics of Tehran in 2022. Participants were 30 patients whom selected by accessible sampling method and randomly assigned to experimental and control groups. The semi-structured clinical interview demographic form and the second version of the Beck depression test were used to collect data. To analyze the hypotheses, ANCOVA was used in SPSS-16. The results indicated that cognitive therapy based on mindfulness is effective on the depressive symptoms in patients with persistent depressive disorder. As a result, the findings support the role of psychological interventions, especially interventions based on changing cognitions and increasing mindfulness in the treatment of persistent depression. Our findings have beneficial implications for psychologists in the treatment of depressed patients.